Analisis Usaha dan Saluran Pemasaran Sagu - Fachrizal, Riza; Ginting, Nina Maksimiliana; Panga, Nurhaya J (AGRICOLA, 2022)
This study was to determine the sago processing process, the income of the sago processing business, the sago marketing channel in Tambat Village. This research will be carried out in Tambat Village, Tanah Miring District, Merauke Regency. The location selection was done purposively with the consideration that Tambat Village is one of the villages that is still actively producing sago. Sources of data using primary data and secondary data. The population is 30 sago processors and the sample is taken by means of a census of 30 sago processors. The data analysis method is used descriptively and the concept of costs and income to the feasibility of the business. The income earned per month is Rp. 3,650,167 with an R/C of 2.2. There are 4 marketing channels used. The first marketing channel is from processors and is directly marketed to consumers, the second marketing channel from processors is directly distributed to collectors and to consumers. The third marketing channel from the processor is distributed to small traders and to consumers. The fourth marketing from the processors is directly distributed to collectors, small traders and directly to consumers.